Digital religious celebrations during and after the Covid-19. Limits and opportunities for regulation (Stato, Chiese e pluralismo confessionale, 2021)
SOMMARIO: 1. The pandemic and the damage occurred to the right of community religious freedom - 2. A survey on the exercise of the worship during lockdown - 3. Digital celebrations: is there a legal regulation?ABSTRACT: During the first phases of the pandemic until today, many religious activities, especially liturgical celebrations, have been suspended and reorganised. Drastic measures and choices were necessary, always in balance with constitutional principles. In this social and historical context, digital platforms seem to have turned into liturgical spaces. The contribution aims to highlight the problems and opportunities that have arisen and to present the practices used within confessional systems, particularly the Catholic one. Also in relation to a research on the subject, promoted by the Giustino Fortunato University, reflections are offered that may favour a better relationship between the needs of worship and liturgical and confessional law in the field of sacraments and celebrations.